2021
DOI: 10.15359/ree.25-3.6
|View full text |Cite
|
Sign up to set email alerts
|

Educación de la inteligencia emocional en edad escolar: Un estudio exploratorio desde la perspectiva docente

Abstract: Introducción. En la actualidad existe una tendencia educativa hacia una pedagogía afectiva. Por ello, en este trabajo se investiga el conocimiento y la experiencia que docentes de educación primaria (alumnado de entre 6 y 12 años) tienen sobre la inteligencia emocional y su educación. Metodología. Un total de 100 docentes de España participan en este estudio transaccional exploratorio. Concretamente, la muestra conseguida a través de una técnica no probabilística de tipo casual ha respondido un cuestionario a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
0
12
0
1
Order By: Relevance
“…Some authors also mentioned that the greater the age the lower the emotional regulation [ 63 ], while other authors have shown that emotional intelligence improve with age [ 9 , 62 , 79 ]. There are also studies highlighting that no statistically significant differences exist with regards to age and emotional intelligence [ 2 , 65 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors also mentioned that the greater the age the lower the emotional regulation [ 63 ], while other authors have shown that emotional intelligence improve with age [ 9 , 62 , 79 ]. There are also studies highlighting that no statistically significant differences exist with regards to age and emotional intelligence [ 2 , 65 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Said authors stated that primary education teachers display higher levels of emotional intelligence compared to infant school teachers. García-Tudela and Marín-Sánchez [ 65 ] contend that both infant education and primary education involve play activities such as gamification and game-based learning, amongst other strategies, that enable work to be carried out with issues linked to emotional intelligence, and which can directly impact teachers’ emotional intelligence. Some authors claim that the educational stage at which teachers teach has no significant difference on the levels of emotional intelligence developed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, emotional education in schools has thus far been approached only scantly and voluntarily in a transversal manner [ 7 , 8 ]. Whilst intervention programmes aimed at students have been implemented at different stages of education, programmes designed for teachers remain few and far between [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%